Comparison of forward light scatter estimations using Shack‐Hartmann spot patterns and a straylight meter. Issue 2 (February 2015) - Lopez, Pablo Benito; Radhakrishnan, Hema; Nourrit, Vincent
Abstract : Purpose : To determine whether an unmodified commercial wavefront aberrometer (irx3) can be used to estimate forward light scattering and how this assessment matches estimations obtained from the C‐Quant straylight meter. Setting : University of Manchester, Manchester, United Kingdom. Design : Prospective comparative study. Methods : Measurements obtained with a straylight meter and with Shack‐Hartmann spot patterns using a previously reported metric were compared. The method was first validated in a model eye by spraying an aerosol over 4 contact lenses to generate various levels of scattering. Measurements with both methods were subsequently obtained in healthy eyes. Results : The study comprised 33 healthy participants (mean age 38.9 years ± 13.1 [SD]). A good correlation was observed between the density of droplets over the contact lenses and the objective scatter value extracted from the hartmanngrams ( r = 0.972, P < .05). However, in eyes of subjects, no significant relationship was found between measurements from the straylight meter and the metric derived from the Shack‐Hartmann method ( r = 0.133, P = .460). Conclusions : The hartmanngrams provided a valid objective measurement of the light scatter in a model eye; the measurements in human eyes were not significantly correlated with those of the light scatter meter. The straylight meter assesses large‐angle scattering, while the Shack‐Hartmann method collates information from a narrow angle around the center of the point‐spread function; this could be the reason for the difference in measurements. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.